The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Multilingualism - Interdisciplinary Topics 2022
DOI: 10.5772/intechopen.98181
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Expectancy-Value Beliefs and Anxiety in Learning Academic Oral English in Bilingual Chinese Postgraduate Students

Abstract: Despite the plethora of research on speaking anxiety, most studies focus on speaking for general purposes in various bilingual contexts, particularly ESL/EFL (English as second/foreign language) contexts. Little research has been done on anxiety when speaking English for academic purposes in bilingual students. Even fewer studies are available on the interaction between academic oral communication (AOC) anxiety and expectancy-value beliefs —important concepts of language learning motivation. Hence, the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 65 publications
1
9
0
Order By: Relevance
“…For example, Xu (2017) found that Chinese first-year undergraduates’ FLA was negatively correlated with their expectancy and intrinsic value but positively connected with attainment value. Other researchers (e.g., Liu and Dong, 2021 ; Zhang, 2021 ) further revealed that expectancy-value motivation could predict FL learning emotions. The longitudinal study by Liu and Dong (2021) revealed that both expectancy and value components of motivation were negative predictors for anxiety experienced by postgraduates learning academic oral English.…”
Section: Literature Reviewmentioning
confidence: 90%
See 4 more Smart Citations
“…For example, Xu (2017) found that Chinese first-year undergraduates’ FLA was negatively correlated with their expectancy and intrinsic value but positively connected with attainment value. Other researchers (e.g., Liu and Dong, 2021 ; Zhang, 2021 ) further revealed that expectancy-value motivation could predict FL learning emotions. The longitudinal study by Liu and Dong (2021) revealed that both expectancy and value components of motivation were negative predictors for anxiety experienced by postgraduates learning academic oral English.…”
Section: Literature Reviewmentioning
confidence: 90%
“…Other researchers (e.g., Liu and Dong, 2021 ; Zhang, 2021 ) further revealed that expectancy-value motivation could predict FL learning emotions. The longitudinal study by Liu and Dong (2021) revealed that both expectancy and value components of motivation were negative predictors for anxiety experienced by postgraduates learning academic oral English. These prior research findings inform that it may be more discreet to consider the relations between FL emotions and expectancy-value motivation as bidirectional since each can play a role in affecting the other, and they both are critical to FL learning success.…”
Section: Literature Reviewmentioning
confidence: 90%
See 3 more Smart Citations